Trauma exposure, mental health and tobacco use among vulnerable Syrian refugee youth in Jordan. (20th November 2019) - Kheirallah, Khalid A; Cobb, Caroline O; Alsulaiman, Jomana W; Alzoubi, Abdallah; Hoetger, Cosima; Kliewer, Wendy; Mzayek, Fawaz
Abstract: Background: Little is known about tobacco use among youth exposed to armed conflicts, or the influence of trauma on tobacco use in this context. This study examined patterns of smoking by tobacco product and gender among Syrian refugee youth living in host communities in Jordan and assessed the associations of post-traumatic stress disorder (PTSD) and depression symptoms, trauma exposure and social support with current smoking status in boys and girls. Methods: Syrian refugee students (mean [standard deviation] age = 14.9 [1.33] years) were identified through the public school system. Data were collected using an online Arabic questionnaire that included questions about demographics, trauma exposure, current smoking (cigarette and waterpipe), PTSD, depression and perceived social support. Logistic regression was used to assess the adjusted effects of independent variables on current smoking status. Results: One in 7 boys and one in 14 girls were current smokers, with boys reporting greater tobacco use than girls. Among boys, current smokers reported significantly higher family member loss and lower perceived family social support than nonsmokers; among girls, current smokers also reported significantly higher family member loss as well as greater PTSD symptoms and lower perceived significant other/special person social support. Conclusions: Tobacco use is established among this vulnerable group. The findings highlight the potential role of psychosocial support for tobacco prevention and cessation strategies.